Persepsi PHBS Karyawan Puskesmas Sumber Pasca diberikan Sosialisasi - Rahma Ardiani; Rezkika Noviyanti; Lutfi Novianti; Etik Marwinda; Rama Nur Fadhila; Permata Ashfi Raihana (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to describe the perception PHBS post employee doing socialization. This study uses qualitative phenomenological methods with semi-structured interview data collection methods. The sampling technique used was purposive sampling. This study consisted of 4 employees of Puskesmas sumber, one person served as the head of the puskesmas, one person served as a public health instructor, one person as coordinator of the midwife, one person as the accountant of the puskesmas. The analytical technique used by the researcher is thematic analysis technique. The results of the research, all informants understood the meaning of PHBS, which is an activity of a healthy and clean lifestyle that must be carried out in daily life. Each informant also has a sad feeling when the community does not comply with the socialization activities that have been provided by the Community Health Center. The results of the research also explain that PHBS activities have begun to be implemented in the community, such as washing hands, wearing masks, and maintaining distance. However, there are still some violations of PHBS.